Solidarity economy in southern Bahia: a look at the territorial policy and technological content (Research, Society and Development, 2020)
The emergence of witches' broom disease in cocoa plantations in the Southern Coastal Territory of Bahia (TLS) caused a change in the agrarian structure of that region: the latifundios were broken down into smaller properties, which were acquired by small farmers or destined for agrarian reform; however, there was no modernization of the production process. In this sense, this article intends to develop a diagnosis of the Solidarity Economy in the TLS and to identify what is the technological content used in the productive process of these enterprises. This analysis is the result of a research involving 147 solidary economic enterprises mapped in the TLS. To obtain the information, questionnaires were applied covering closed questions and with multiple choices. The research is characterized as descriptive with a deductive approach, and with qualitative and quantitative treatment for presenting the data generated by the interviews. The results indicate that none of them have an entrepreneurial culture and do not use forms of technological innovation, in addition to having an artisanal matrix of the means of production, which puts their survival at risk.